Searching for the Sense of National Identity in the Globalization Context – Example of Students in Croatia - Sakač, Marija D.; Štrangarić, Snežana Z.; Marković, Saša S. (Collection of Papers of the Faculty of Philosophy in Priština, 2017)
The results of an empirical research on national identity and its components are presented in this paper. National identity was measured by the scale NAIT-K, which contains National identity scale NAIT with elements of MEIM (Phinney, 1992) and National identity scale (Cinnirella, 1997). Both instruments had high results for Cronbach alfa (α=0, 92; α=0, 87). In addition to these instruments, socio-demographic questionnaire was also used. On the sample of 209 students at Faculty of Philosophy in Zagreb, results indicated medium strong national identity. The factor analysis of the structure of national identity measured by NAIT-K isolated five components. We defined them as: strong national identity, nationalism, cosmopolitism, conative dimension of national identity and nation loyalty as a form of traditional heritage. Statistically significant differences are determined in analyses of national identity and religiosity. It was shown that religious respondents have stronger national identity compared to nonreligious ones.